Correlation between fibre content of the lung and disease in east London asbestos factory workers. - Wagner, J C (1988)
The lungs from 36 past workers at an east London asbestos factory who had died from asbestos related disease were compared with lung tissue from 56 matched control patients being operated on in east London for carcinoma of the lung, correlating the severity of asbestosis and the presence of pulmonary carcinoma or mesothelioma of the pleura or peritoneum with an asbestos exposure index and type and amount of mineral fibre in the lungs. Asbestosis was associated with far heavier fibre burdens than mesothelioma. There was also a striking difference in the degree of asbestosis between the subjects with mesothelioma and those with carcinoma of the lung, the asbestosis being more severe in the latter. A further finding was that crocidolite and amosite were strongly associated with asbestosis, carcinoma of the lung complicating asbestosis, and mesothelioma, whereas no such correlation was evident with chrysotile or mullite. It is suggested that more emphasis should be placed on the biological differences between amphibole and serpentine asbestos fibre.